Exploring the impact of formulation and temperature shock on metered dose inhaler priming. Issue 1 (2nd January 2017) - Lewis, David A.; O'Shea, Helen; Mason, Francesca; Church, Tanya K.
ABSTRACT: The interplay between canister, valve design, formulation, and environmental temperature is crucial to dose retention in metered dose inhalers (MDIs). Previous studies that have utilized MDIs with polymeric capillary retention valves, have shown that exposure to environmental changes can create a temporary temperature gradient between the formulation retained in the metering chamber and the formulation reservoir in the metal canister, which can cause inconsistencies in the dose delivered to the patient. The purpose of this study was to more fully quantify these effects. This was achieved by deliberately varying the temperature difference between inhalers and environment within ranges representative of routine usage, and assessing the resulting loss of prime effect via shot weight and delivered dose testing. The shot weights delivered by three fixed-dose commercial MDIs—Foster®, flutiform® and Seretide®, were investigated under different experimental conditions. Exposure to temperature changes of up to 15°C did not appear to affect unprimed shot weights (USW) or subsequent doses from the Foster product. In contrast, flutiform maintained prime at a temperature differential of 8.6°C, but delivered a low USW following exposure to a ΔT of 15°C under both realistic and controlled conditions. Seretide exhibited loss of prime at lower temperature differentials (ΔT 8.6°C) and a reduction in USW. The results suggest that the inclusion of ethanol in a solution-based formulation may inhibit loss of prime, leading to more robust performance in the face of temperature variations. Delivered dose testing was carried out to assess the effect of loss of prime on the device ability to deliver a dose to within 80–120% of the label claim. The results suggest that the drainage of propellant from the metering chamber of suspension MDIs leaves active pharmaceutical ingredient (API) residue, causing an increase in subsequent doses once the prime has been restored. Taken together, the results provide valuable insight into the likely performance of MDIs subjected to routine daily use, highlighting design and formulation strategies that could be applied to make performance more robust.